2023
DOI: 10.3390/en16073159
|View full text |Cite
|
Sign up to set email alerts
|

Testing and Analysis of Selected Operating Parameters of a Vehicle Powered by Fuel with the Addition of Biocomponents

Abstract: The most common fuel used for powering compression ignition engines is diesel, whose main components are petroleum products. The constantly growing energy demand involves the implementation of new technical solutions and applying alternative fuels, including renewable ones, such as rapeseed oil, sunflower oil, peanut oil, and animal fats. The most commonly used biofuels are those obtained from chemically processed rapeseeds (transesterification) to provide them with physical–chemical properties similar to dies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It should be emphasized that our obtained results align with the results presented in the works of Prof. W. Lotko [7,15,18]. In addition, other studies have confirmed that it is possible to use biodiesel to power diesel engines [8,9,19,20]. The calculation model presented in this study can also be used for thermal calculations of the supercharged engine and in the analysis of other biofuels.…”
Section: Conclusion and Further Workmentioning
confidence: 68%
“…It should be emphasized that our obtained results align with the results presented in the works of Prof. W. Lotko [7,15,18]. In addition, other studies have confirmed that it is possible to use biodiesel to power diesel engines [8,9,19,20]. The calculation model presented in this study can also be used for thermal calculations of the supercharged engine and in the analysis of other biofuels.…”
Section: Conclusion and Further Workmentioning
confidence: 68%
“…This could be applied to both gasoline and diesel in low-level blends. The main advantages of biodiesel favorable to friction are enhanced scuffing protection performance, effective film formation, and the presence of unsaturated fatty acid compounds [20], while there are also some disadvantages like oxidation, instability of properties, moisture absorption, acidic nature, etc. [21].…”
Section: Introductionmentioning
confidence: 99%